Evaluating Students' COVID-19 Knowledge, Attitudes and Practices (COVKAP) during the COVID-19 Pandemic - David R. Axon; Alina Cernasev; Meghana Desai; Sharon E. Connor; Lauren J. Jonkman; M. Chandra Sekar (MDPI AG, 2022)
The COVID-19 pandemic led to significant disruption in students' lives through lockdowns, restricted movement, remote instruction, and mixed information. Therefore, this study aimed to capture the knowledge, attitudes, and practices of student pharmacists during 2020-2021. A 43-item COVID-19 Knowledge, Attitudes, and Practices (COVKAP) survey previously developed was administered at four schools of pharmacy across the U.S. during Fall 2020 and Spring 2021. A total of 418 responses were analyzed from graduating classes of 2021-2024. There were no significant differences in correct COVID-19 knowledge responses across the four graduating years. Respondents' attitudes around COVID-19 were homogenous with the exception for their belief in their preparedness to administer COVID-19 vaccines. Respondents reported wearing masks daily (76.8%), infrequently visiting restaurants (82.1%), practicing social distancing daily (45.7%), and referring to medical journals for information (72%). In conclusion, during the pandemic, student pharmacists experienced significant changes in their academic lives. Their knowledge and subsequent attitudes and practices were consistent with the state of evidence during Fall 2020 and Spring 2021. Subsequently, as newer information has emerged, the authors suggest that the COVKAP survey may be modified and administered frequently to address student needs and concerns as the pandemic evolves.